The Third-order Iterative Method for Solving Nonlinear Equations - Comemuang, Chalermwut; Wisesram, Naratip; Pongsawat, Natthapoom (Naresuan University Journal: Science and Technology (NUJST), 2022)
In this paper, we present a new iterative method for solving nonlinear equations, which were developed from the concept of Rafiq et al. The new method is based on Newton’s method and using Taylor’s Series to prove the convergence of the method. This iterative method requires three evaluations of the function, and only use the first derivative. Analysis of its convergence shows that the order of convergence of the new iterative method is third. Numerical comparisons are made with other methods to show the efficiency of the proposed method. Keywords: Nonlinear equations, Newton’s method, Oder of convergence, Iterative method